AN ANALYSIS OF WORD FORMATION PROCESSES IN OUTDOOR ADVERTISEMENT OF BILLBOARD FOUND IN LAMONGAN - Nurman, Moh (Universitas Islam Lamongan, 2016)
As the term word-formation are dealing with the formation of words. Word formation process has ten categories are the followings: Coinage, Borrowing, Compounding, Blending, Clipping, Back Formation, Conversion, Acronym, Inflection and Derivation.Keywords: word formation, advertisement and billboard